L'expérience de retour au travail des personnes vieillissantes ayant subi une atteinte à la santé : un examen de la portée. Issue 1 (2nd March 2023) - Lecours, Alexandra; Bédard-Mercier, Roxanne
Abstract: Aging workers represent an emerging, growing, and essential population for the contemporary labour market. Considering their unique characteristics, these individuals are at risk of experiencing periods of disability at work due to different reasons (e.g., chronic diseases, occupational injuries) and a different return-to-work experience compared to younger workers. The scoping review presented in this article aimed to identify facilitators and barriers to returning to work in aging people who suffered a health impairment. Information from 34 manuscripts was extracted and analyzed, enabling the identification of factors hindering and facilitating the return to work of aging individuals, with regard to four systems: the individual, work, health, and compensation. The results suggest levers accessible to the various stakeholders involved in the process of returning to work for aging individuals to promote their healthy, safe, and satisfactory participation in work after a period of disability.